Explaining IMF lending decisions after the Cold War - Christoph Moser; Jan-Egbert Sturm (ETH Zurich, KOF Swiss Economic Institute, 2011)
This paper empirically investigates the economic and political factors that affect a country's likelihood to sign an arrangement with the IMF and the determinants of the financial size of such a program. Arguably the world and the global financial architecture underwent structural changes after the ending of Cold War and so did the role of the IMF. Hence, we update and extend the work of Sturm et al. (2005) by employing a panel model for 165 countries that focuses on the post-Cold War era, i.e., 1990-2009. Our results, based on extreme bounds analysis, suggest that some economic and political variables are robustly related to these two dimensions of IMF program decisions. Furthermore, we show that it is important to distinguish between concessional and non-concessional IMF loans.
Keywords: O19; F33; 330; IMF; lending facilities; extreme bounds analysis